Sustainable Development and World Politics - A. Ursul; D. Kalyuzhnaya (Vestnik MGIMO-Universiteta)
The article points out that the progressive deterioration of the social and environmental situation on the planet and the emergence of the real threat of anthropo-ecological catastrophe necessitate the abandoning of the current model of civilizational development and the formation (first in theory and then in practice) of an ultimately new one. This innovative strategy, which means taking account of the main socio-natural contradiction, is called a sustainable development strategy. This new form of civilizational development must become rationally governed on a planetary scale, thus providing the survival and temporal continuation of the existence of humans and biosphere. The authors regard sustainable development as a vitally important (later on - dominating) orientation of international, political and global processes. This vision makes it crucially important to embed this conception into the proper scientific disciplines and research fields. The authors make use of the A.D. Bogaturov's conceptualization approach for the scientific discipline of world politics and consider the latter as an evolutionary form of global political development. The real global integrity of the world political system serves as a global attractor of this evolutionary transformation, and this aspect represents the specific pattern of all global processes. It is supposed that these processes will unfold through transition to sustainable development. The development of the global system of political actorship is considered a fundamental process within the growth of overall complexity of the global political structure. In the evolutionary sustainable development perspective it should result in the formation of an integral subject of global politics and global activity. The article shows that the dominating state-centric approach reproduces the political model of unsustainable development, which is characterized by archaic prerequisites of political realism, spontaneous formation of system, and growing threats to global security.